HUBUNGAN KEPADATAN LALAT, PERSONAL HYGIENE DAN SANITASI DASAR DENGAN KEJADIAN DIARE PADA BALITA DI LINGKUNGAN I KELURAHAN PAYA PASIR KECAMATAN MEDAN MARELAN KOTA MEDANTAHUN 2015 - sarah safira; nurmaini *; surya dharma (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Diarrhea is one of public health’s problem with high mortality and morbidity rate especially among children under five years old in Indonesia. There were 158 cases of the incidence of diarrhea in Lingkungan I Kelurahan Paya Pasir Kecamatan Medan Marelan Medan city in 2014. The aim of this study was to analyze the relationship between the density of flies, personal hygiene and basic sanitation with the incidence of diarrhea in children under five years old. This study method is analytical survey with cross sectional design. Samples were chosen using total sampling technique, that there were 77 children under five years old and the mother as a respondent. The density of flies is measured by using fly grill, personal hygiene were obtained through interview using questionnaires and the datas of basic sanitation is collected through direct observation using basic sanitation’s observation sheets. The study result that there were found 33 children under five years old got diarrhea in the last one month (period of April to May 2015). In chi square test results obtained the value of p=0,044 and PR=1,387 for the density of flies variable, p=0,003 and PR=1,623 for personal hygiene variable and p=0,034 and PR=1,158 for basic sanitation variable. The high density of flies can be caused by bad environmental sanitation. Washing hand’s habit using soap among respondent is very poor. That was because most respondents have last educated in junior high school and lack of knowledge about personal hygiene. The basic sanitation owned by respondent mostly in the category of unqualified health. The conclusion is there are a correlation between the density of flies, personal hygiene and basic sanitation to diarrhea in children under five years old. It is advisable to the respondents (mother of children under five years old) to be more concerned about their own personal hygiene and their children. Sanitation Office and the goverment is suggested to be more concerned to citizens who live around disposal area of garbage Terjun especially in basic sanitation’s condition.